Ketersediaan Energi Ransum yang Mengandung Wheat Pollard Hasil Olahan Enzim Cairan Rumen yang Diproses Secara Steam Pelleting pada Ayam Broiler - W W Wardani; N Ramli; W Hermana (Media Peternakan, 2004)
Wheat pollard is a common feed ingredient, but its non starch polysaccharide component is still a limiting factor as an anti nutrition. The combination treatment of enzymes from rumen liquor (DE) and steam pelleting (SP), could change non-starch polysaccharide structure to be more digestible for broiler chicken. Twenty seven broiler chicken of 37 days old were divided into 27 experimental unit and randomly offered one of 9 treatments, that were R1 (DE 0 U/kg + 600C), R2 (DE 0 U/kg + 800C), R3 (DE 0 U/kg + 1000C), R4 (DE 620 U/kg + 600C), R5 (DE 620 U/kg + 800C), R6 (DE 620 U/kg + 1000C), R7 (DE 1.240 U/kg + 600C), R8 (DE 1.240 U/kg + 800C) and R9 (DE 1.240 U/kg + 1000C). The chicken have been fasted for 24 hours and fed by force feeding 30 g/head while water was offered ad libitum. Apparent Metabolizable Energy (AME), Nitrogen Corrected Apparent Metabolizable Energy (AMEn), True Metabolizable Energy (TME), Nitrogen Corrected True Metabolizable Energy (TMEn) and Nitrogen Retention were determined. Three chickens were used for collecting nitrogen and endogenous energy. Data were analyzed by analysis of variance according to completely randomized design with factorial 3x3 and Duncan’s Multiple Range Test. Enzymes dosage and steam treatment did not influence metabolizable energy (AME, AMEn, TME and TMEn) and nitrogen retention. Combination of enzymes (R4 and R8) and steam temperature treatment increased AME, AMEn, TME and TMEn but did not increase nitrogen retention. The result indicated that combination of enzymes at dosage of 620 U/kg with steam 600C treatment increased the metabolizable energy of wheat pollard based diets. Key words: liquor rumen enzymes, pelleting, energy, nitrogen, broiler